Factors Affecting the Intention of Accounting Students as Academic Whistleblowers: Study on Undergraduate Accounting Students of Tadulako University - Ikke Nurhasanah; Muhammad Ansar; Jurana Jurana; Sugianto Sugianto (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyse the factors that influence accounting students' intention to become academic whistleblowers, with a focus on undergraduate accounting students at Tadulako University. The study employs a quantitative method, utilizing data collected from 81 respondents via a Google Form questionnaire. The data were then analysed using the Partial Least Squares (PLS) method, with the support of SmartPLS 4.0 software. The variables examined include subjective norms, attitudes toward behaviour, and perceptions of behavioural control. The study's findings reveal that subjective norms, which represent societal and peer influences, do not have a significant impact on students' intention to act as academic whistleblowers. In contrast, attitudes toward behaviour and perceptions of behavioural control both play a crucial role in shaping this intention. Among these variables, perceptions of behavioural control emerged as the most influential factor, suggesting that students' ability to control their actions and their confidence in handling academic misconduct are critical in fostering their intention to report such behaviour. This highlights the importance of not only promoting positive attitudes toward academic integrity but also strengthening self-control and personal efficacy. Educational institutions, therefore, should focus on enhancing students' self-efficacy and providing appropriate channels and support to facilitate whistleblowing. Encouraging positive attitudes and offering training on self-control can help create an environment where students feel empowered to report academic misconduct without fear of retaliation. This research provides valuable insights for universities and policymakers to develop strategies for improving academic ethics, particularly in relation to reporting and preventing academic misconduct.